THE THE INFLUENCE OF THE EXCIPIENTS ON THE ANTI-INFLAMMATORY EMULGEL BIOPHARMACEUTICAL QUALITY PARAMETERS - NATALIA B DEMINA; ELENA O BAKHRUSHINA; IVAN I KRASNYUK; MIKHAIL B KORNEEV (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Boswellia serrata dry extract (BSDE) has clinically proved its anti-inflammatory, anti-gout, and analgesic effect. In the course of this study, compositions and technologies of the emulgels, containing dry Boswellia extract, were developed. Materials and Methods: Rheological characteristics of gels were determined with rotational viscosity method using coaxial rotation viscometer Lamy Rheology RM 200. The stickiness was determined using a lever mechanism which separates two preprocessed glass plates of the same area from each other. Spreadability was determined with a weighted amount of gel placed on a glass plate (10 cm × 10 cm), covered with a cover glass of the same size and a 100 g measuring plane placed on top of it. Results: The composition containing 20% of turpentine oil was shown to have the highest yield strength, which can positively affect the aggregative stability of the dosage form. The spreadability of all samples lies within the average value of the spreadability of the commercial gels. The stickiness of all samples was determined to be in the range from 3.6 to 4.9 N. The composition containing turpentine oil showed maximum stickiness after application and its minimum decrease by 5 min. Conclusion: The advantages of the composition including turpentine oil as a solvent for BSDE were experimentally established.